Identification of serve pacing strategies during five-set tennis matches - Martin, C.; Bideau, B.; Touzard, P.; Kulpa, R. (International Journal of Sports Science & Coaching, 2019)
This study aims to investigate the prominence of different pacing strategies adopted by male professional tennis players during five-set matches and their relationship with match outcome, ATP ranking and Grand Slam tournament. Fifty five-set matches of the 2014 Grand Slam tournaments were analyzed. First and second serve velocities, percentages of first serve in, and percentages of first and second serve points won were collected for each of the five sets. According to the fluctuations of mean first serve velocity for each of the five sets, players were classified into five types of pacing strategies: `variable`, `parabolic`, `constant`, `all-out` and `negative-split`. Professional players mostly used `variable` pacing strategy (45%), followed by `parabolic` (20%), `constant` (18%) and `all-out` (15%) strategies, which are closely distributed. Finally, `negative-split` strategy (2%) is infrequently used. The pacing strategy used by players tends to exert an influence on match outcome (P = 0.072). There is no significant association between players` ranking and type of pacing strategy used (P = 0.384). There is no significant association between Grand Slam tournaments and type of pacing strategy used (P = 0.875). Serve velocity and serve points won are significantly decreased in losers, while they are increased or kept constant in winners during the fifth set of the match. `Negative split`, `variable` and `parabolic` strategies seem to be the most effective for winning five-set match, while `all-out` strategy appears ineffective since when players used it, they lost the match in 73% of cases. Moreover, tennis players should consider physical conditioning programs to avoid decreases in serve velocity and percentage during the fifth set of a tennis match.